Screening of Trauma Patients in Need of Knee Radiography by Triage Nurses and Using Ottawa Knee Rule; a Letter to Editor - Samad Shams Vahdati; Alireza Ala; Zhila Samani; Sasan Ghazanfar Ahari; Mohammad Mirza-Aghazadeh-Attari (Archives of Academic Emergency Medicine, 2019)
In some clinical guidelines, emergency triage nurses request radiographies according to the clinical decision-making priorities. While some studies have suggested that nurses are not as accurate as doctors in assessing major complications of trauma to the knee, it is thought that they are as capable in detecting minor traumas and inconsequential episodes (1). Many studies have shown that the cost of treatment and the waiting period for patients in the emergency department decrease without missing fractures when traumas are initially assessed by a certified nurse. Routinely, a clinical criteria termed Ottawa Knee Rule is utilized to determine if a patient is in need of a knee radiography or not (2, 3). According to this guideline, if a patient with suspected knee trauma meets any of the following criteria, he or she should undergo imaging modalities: Age above 55 years, tenderness at head of fibula, isolated tenderness of patella, inability to flex the knee more than 90Â°, and inability to bear weight (4).